PASC in Solid Organ Transplant Recipients With Self-reported SARS-CoV-2 Infection. Issue 1 (19th September 2022) - Alasfar, Sami; Chiang, Teresa Po-Yu; Snyder, Andrew J.; Ou, Michael T.; Boyarsky, Brian J.; Abedon, Aura T.; Alejo, Jennifer L.; Cook, Sydney; Cochran, Willa; Brigham, Emily; Parker, Ann M.; Garonzik-Wang, Jacqueline; et al.
Abstract : Background: Postacute sequelae of SARS-CoV-2 infection (PASC) is an increasingly recognized phenomenon and manifested by long-lasting cognitive, mental, and physical symptoms beyond the acute infection period. We aimed to estimate the frequency of PASC symptoms in solid organ transplant (SOT) recipients and compared their frequency between those with SARS-CoV-2 infection requiring hospitalization and those who did not require hospitalization. Methods: A survey consisting of 7 standardized questionnaires was administered to 111 SOT recipients with history of SARS-CoV-2 infection diagnosed >4 wk before survey administration. Results: Median (interquartile range) time from SARS-CoV-2 diagnosis was 167 d (138–221). Hospitalization for SARS-CoV-2 infection was reported in 33 (30%) participants. Symptoms after the COVID episode were perceived as following: significant trauma (53%), cognitive decline (50%), fatigue (41%), depression (36%), breathing problems (35%), anxiety (23%), dysgeusia (22%), dysosmia (21%), and pain (19%). Hospitalized patients had poorer median scores in cognition (Quick Dementia Rating System survey score: 2.0 versus 0.5, P = 0.02), quality of life (Health-related Quality of Life survey: 2.0 versus 1.0, P = 0.015), physical health (Global physical health scale: 10.0 versus 11.0, P = 0.005), respiratory status (Breathlessness, Cough and Sputum Scale: 1.0 versus 0.0, P = 0.035), and pain (Pain score: 3 versus 0 out of 10, P = 0.003). Among patients with infection >6 mo prior, some symptoms were still present as following: abnormal breathing (42%), cough (40%), dysosmia (29%), and dysgeusia (34%). Conclusions: SOT recipients reported a high frequency of PASC symptoms. Multidisciplinary approach is needed to care for these patients beyond the acute phase.